Tourism as a diversification factor for the economy of Kemerovo region – Kuzbass - Кирилл Бобко; Олег Затепякин; Татьяна Бобко (Вестник Пермского университета: Серия Экономика)
Introduction. At present, the US and EU sanctions imposed on the Russian fuel and energy sector of the economy have a negative impact on the economic growth rates of primary regions where the goods of the extractive industries dominate the GRP structure. Low mineral production reduces the cost-efficiency of regional budgets, as it sets the barriers in financing social programs, infrastructure projects, etc. To increase the sustainability of the territory's development, it is important to study the relationship between production indicators and the revenue of the regional budget, and find the factors for diversifying the sectoral structure of the economy to ensure long-term financial stability of the region. Purpose. The study aims at justifying the need to use domestic resources as the key factor of industry diversification to increase sustainability of economic development for a resource-based region. Hypothesis. Tourism development could be one of the opportunities for better sustainability of the economy and budget revenues of Kemerovo Region-Kuzbass. Materials and Methods. The study refers to thematic review of sources, analysis of statistical data, case studies, and comparative analysis. Results and Conclusions. The paper examines the factors influencing the sustainable performance of national and foreign territories. The authors explored the determinants of better regional sustainability identified by national and foreign scientists. The authors also identified the trends of growth/decline in production of national extractive industries and their impact on the structure of tax collections in the Russian Federation and looked at the concerns of resource regions with the greatest decline in tax collections. The foreign and national practices of sectorial diversification are analyzed. The key problem of the sectorial structure of Kemerovo region-Kuzbass’s economy is identified; the need for its diversification is substantiated. Changes in the external and internal environment show the need for developing the tourism industry as a significant factor for better sustainability of the regional economy. The authors proposed to establish a digital ecosystem called Tourism and Industry of Hospitality in Kemerovo Region – Kuzbass with the support of the regional government to boost the growth of tourism.